2011
DOI: 10.1093/annonc/mdr002
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of pemetrexed in combination with cetuximab and concurrent radiotherapy in patients with head and neck cancer

Abstract: The addition of pemetrexed 500 mg/m(2) to cetuximab and radiotherapy is recommended for further study in not previously irradiated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Conversely the MTHFR-A1298A genotype was associated with significantly shorter OS in patients with recurrent or metastatic head and neck cancer treated within a phase II trial of pemetrexed and bevacizumab [27]. However, both MTHFR-A1298C and the MTHFR-C677T SNP did not correlate with response rate, survival or severity of treatment-related toxic effects in patients with head and neck cancer treated with pemetrexed in combination with cetuximab and concurrent radiotherapy [28].…”
Section: Discussionmentioning
confidence: 83%
“…Conversely the MTHFR-A1298A genotype was associated with significantly shorter OS in patients with recurrent or metastatic head and neck cancer treated within a phase II trial of pemetrexed and bevacizumab [27]. However, both MTHFR-A1298C and the MTHFR-C677T SNP did not correlate with response rate, survival or severity of treatment-related toxic effects in patients with head and neck cancer treated with pemetrexed in combination with cetuximab and concurrent radiotherapy [28].…”
Section: Discussionmentioning
confidence: 83%
“…This suggested that there are several plausible mechanisms to explain the increased rate of infectious complications in advanced cancer patients treated with cetuximab. EGF and EGF-like protein families, such as heparin-binding EGF-like growth factor (HB-EGF), are essential for cell proliferation, differentiation, and wound healing [25], [26]. Cetuximab may target the bone marrow EGF receptors, which are expressed on he surface of neutrophils and play key roles in their proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these patients were treated with cetuximab plus cisplatin/paclitaxel/radiotherapy (UPCI 05-003, ref. 17) or cetuximab plus pemetrexed/radiotherapy (UPCI 05-005, ref. 18).…”
Section: Methodsmentioning
confidence: 99%